Zinc-α2-Glycoprotein Exerts Antifibrotic Effects in Kidney and Heart - Soerensen-Zender, Inga; Bhayana, Sagar; Susnik, Nathan; Rolli, Veronique; Batkai, Sandor; Baisantry, Arpita; Bahram, Siamak; Sen, Payel; Teng, Beina; Lindner, Robert; Schiffer, Mario; Thum, Thomas; et al. (Journal of the American Society of Nephrology, 2015)
Zinc-α2-glycoprotein (AZGP1) is a secreted protein synthesized by epithelial cells and adipocytes that has roles in lipid metabolism, cell cycling, and cancer progression. Our previous findings in AKI indicated a new role for AZGP1 in the regulation of fibrosis, which is a unifying feature of CKD. Using two models of chronic kidney injury, we now show that mice with genetic AZGP1 deletion develop significantly more kidney fibrosis. This destructive phenotype was rescued by injection of recombinant AZGP1. Exposure of AZGP1-deficient mice to cardiac stress by thoracic aortic constriction revealed that antifibrotic effects were not restricted to the kidney but were cardioprotective. In vitro, recombinant AZGP1 inhibited kidney epithelial dedifferentiation and antagonized fibroblast activation by negatively regulating TGF-β signaling. Patient sera with high levels of AZGP1 similarly attenuated TGF-β signaling in fibroblasts. Taken together, these findings indicate a novel role for AZGP1 as a negative regulator of fibrosis progression, suggesting that recombinant AZGP1 may have translational effect for treating fibrotic disease.
EVALuna2:34563